Isolasi Bakteri Endofit dari Tanaman Sirih Hijau (Piper betle L.) dan Potensinya sebagai Penghasil Senyawa Antibakteri - Ukhradiya Magharaniq Safira; Fachriyan Hasmi Pasaribu; Maria Bintang (IPB University, 2014)
Endophytic bacteria are beneficial microorganisms that interact with host plants without causing disruption or damage to the host. Some studies suggest that certain endophytic bacteria can produce chemical compounds that have an effect on health, especially endophytic bacteria isolated from medicinal plants. Green betel (Piper betle L.) is a medicinal plant that has been used for years and has many benefits. The purposes of this study are to isolating and screening of endophytic bacteria from green betel against four pathogenic bacteria (Staphylococcus aureus, Escherichia coli, Bacillus cereus and Salmonella enteritidis). The number of endophytic bacteria that has been isolated are 14 isolates. Based on the screening results, three isolates of endophytic bacteria have potential activity (characterized by the formation of inhibition zone) against S. aureus. The inhibition zone may indicate that those isolates produce compounds that have antibacterial effects. Those isolates are AS1, BS1 and BS2. The biggest inhibition zone showed by BS1, so it can be concluded that BS1 is the most potential isolate as a novel source of antibacterial compound.